Experimental investigation of the impacts of selective exhaust gas recirculation on a micro gas turbine. (November 2019) - Bellas, Jean-Michel; Finney, Karen N.; Diego, Maria Elena; Ingham, Derek; Pourkashanian, Mohamed
Highlights: Selective exhaust gas recirculation (S-EGR) was investigated at pilot scale. S-EGR tests with relevant CO2 enhancement levels were carried out. Electrical efficiency and rotational speed reduced slightly under S-EGR conditions. CO and UHC emissions increased with S-EGR, mainly at low power outputs. NOx emissions tended to fall under S-EGR conditions. Abstract: Selective exhaust gas recirculation (S-EGR) is an option proposed to augment the CO2 content in the flue gases of gas-fired systems, facilitating integrated post-combustion CO2 capture. However, issues such as flame instabilities and increases in unburned species require careful analysis. The performance of a micro-gas turbine under simulated S-EGR conditions is evaluated here. Maximum flue gas CO2 concentrations of 8.4 and 10.1 vol% were achieved at power outputs of 100 and 60 kWe, respectively; a 4–7 times increase in CO2 content compared to the baseline cases – similar to what can be achieved with S-EGR systems. Impacts on the operational performance of the system were assessed, together with the resulting CO, unburned hydrocarbon and nitrogen oxide (NOx) emission trends. The electrical efficiency reduced slightly under S-EGR conditions and emissions of unburned and partially oxidised species increased, especially at lower loads, where incomplete combustion effects were more prominent. The rotational speed of the engine decreased under S-EGR conditions as a result of the change in the oxidiser properties, with the compressor discharge temperatures also decreasing slightly. Furthermore, NOx emissions were lower in S-EGR scenarios due to the expected lower flame temperatures, which leads to reduced thermal NOx production.